AB0574 A MONOGENIC DISEASE WITH WIDE RANGE OF SYMPTOMS: DEFICIENCY OF ADENOSINE DEAMINASE 2. (June 2019) - Batu, Ezgi Deniz; Taskiran, Ekim Z.; Özkara, Hatice Asuman; Ünal, Şule; Guleray, Naz; Erden, Abdulsamet; Karadag, Omer; Gümrük, Fatma; Çetin, Mualla; Bilginer, Yelda; Sonmez, Hafize Emine; Ayvaz, Deniz Cagdas; et al.
Abstract : Background: Deficiency of adenosine deaminase 2 (DADA2) is an autosomal recessive autoinflammatory disorder caused by ADA2 mutations. Objectives: We aimed to investigate the characteristics of DADA2 patients along with the ADA2 enzyme levels. Methods: 24 DADA2 patients who admitted to the Adult and Pediatric Rheumatology, Pediatric Haematology, and Pediatric Immunology Departments were included. All exons of the ADA2 gene were screened by Sanger sequencing in all DADA2 patients. Serum ADA2 enzyme activity was measured by modified spectrophotometric method. Results: 24 DADA2 patients were included; Group 1, 14 DADA2 patients with polyarteritis nodosa (PAN)-like phenotype; Group 2, 9 patients with Diamond-Blackfan anemia (DBA)-like features and one with immune deficiency. 14 PAN-like DADA2 patients did not have the typical thrombocytosis seen in classical PAN. Inflammatory attacks were evident in only Group 1 patients. Serum ADA2 was low in all DADA2 patients except one who was tested after hematopoietic stem cell transplantation. There was no significant difference in ADA2 levels between PAN-like and DBA-like DADA2 patients (Figure 1 ). ADA2 activities of heterozygote family members were about half the level of the control subjects. However, in heterozygote DADA2 patients, serum ADA2 levels were as low as the ones of homozygote DADA2 patients. ADA2 mutations were affecting the dimerization domain in Group 1 patients and in the catalytic domain in Group 2 patients (Table 1 ). Conclusion: We suggest that enzyme activity of ADA2 should be assessed along with genetic analysis since there are heterozygote patients with absent enzyme activity. Our data confirms a possible genotype phenotype correlation where dimerization domain mutations are associated with a PAN-like phenotype whereas catalytic domain mutations are associated with hematological manifestations. References: [1] Navon Elkan P, et al. Mutant ADA2 in a PAN vasculopathy. N Engl J Med 2014;370(10):921-931 [2] Zhou Q, et al. Early-onset stroke and vasculopathy associated with mutations in ADA2. N Engl J Med 2014;370(10):911-920 Acknowledgement: This study was supported by Scientiﬁc and Technological Research Council of Turkey (TÜBITAK) with grant numbers of 315S192. Prof. Nurten Akarsu performed the molecular studies of DBA patients and special thanks to her for great support. Disclosure of Interests: Ezgi Deniz Batu: None declared, Ekim Z. Taskiran: None declared, Hatice Asuman Özkara: None declared, Şule Ünal: None declared, Naz Guleray: None declared, Abdulsamet Erden: None declared, Omer Karadag: None declared, Fatma Gümrük: None declared, Mualla Çetin: None declared, Yelda Bilginer: None declared, Hafize Emine Sonmez: None declared, Deniz Cagdas Ayvaz: None declared, Ilhan Tezcan: None declared, Seza Özen Consultant for: Seza Ozen is receiving consultancy fees from Novartis, Speakers bureau: Roche